1991
DOI: 10.1002/ccd.1810220103
|View full text |Cite
|
Sign up to set email alerts
|

Application of coronary angioplasty to the septal perforator arteries

Abstract: Significant coronary artery disease affecting the septal perforator arteries can cause anginal pain, rhythm disturbances, or septal infarction. However, since these vessels are usually inaccessible to coronary bypass surgery, there is a tendency among angiographers and angioplasters to overlook lesions of the septal perforator arteries. Our experience suggests that if medical treatment is not sufficient to treat clinical manifestations resulting from septal perforator disease, then coronary angioplasty can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…One approach is revascularization by means of POBA. 1,[6][7][8][9]12 In the largest relevant study (21 patients), 1 POBA of a large SPB had a 95% success rate. However, other investigators reported that intervention in the SPB can lead to acute vessel occlusion and complete heart block, either immediately or later.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…One approach is revascularization by means of POBA. 1,[6][7][8][9]12 In the largest relevant study (21 patients), 1 POBA of a large SPB had a 95% success rate. However, other investigators reported that intervention in the SPB can lead to acute vessel occlusion and complete heart block, either immediately or later.…”
Section: Discussionmentioning
confidence: 94%
“…[2][3][4][5] Revascularization by means of percutaneous coronary intervention (PCI) to the SPBs can be technically challenging when the SPBs have a caliber <2 mm or a sharply angulated takeoff, because it is difficult to deliver devices of appropriate size. Various approaches to PCI, with or without SPB stenting, have been reported [1][2][3][6][7][8][9][10] ; however, their clinical effectiveness and long-term outcomes are not known. 1 Existing guidelines lack recommendations for interventions in diseased SPBs.…”
mentioning
confidence: 99%
“…The revascularization of substantial SPB stenosis using POBA has been described in several studies [1][2][3][4][5][6][7]. Reported by the largest sample-size study involving 21 patients, Vemuri et al associated significant large SPB POBA with a 95% success rate (a number similar to that of major epicardial coronary arteries) [1].…”
Section: Discussionmentioning
confidence: 99%
“…Reported by the largest sample-size study involving 21 patients, Vemuri et al associated significant large SPB POBA with a 95% success rate (a number similar to that of major epicardial coronary arteries) [1]. Nevertheless, other investigators reported acute vessel occlusion and complete heart block following this approach at an earlier or a later stage [3,4]. Since SPB obstructive lesions tend to be ostial, revascularization utilizing POBA may carry the risk of restenosis secondary to elastic recoil [5].…”
Section: Discussionmentioning
confidence: 99%
“…Angiography with PCI has shown some success, although current literature suggests that in-stent stenosis rates are elevated when compared with stenting of other coronary vessels. 2,4,7,8 Unfortunately, there is currently no role for coronary artery bypass grafting given the inaccessible, interior course of these arteries. Case reports have suggested a possibility for aspiration thrombectomy as a solution, although further research is needed before this option is used more widely.…”
Section: Discussionmentioning
confidence: 99%